A surface transition of nanoparticle-decorated graphene films from water-adhesive to water-repellent. Issue 36 (11th September 2018) - Wan, Shu; Wan, Hao; Bi, Hengchang; Zhu, Jingfang; He, Longbing; Yin, Kuibo; Su, Shi; Sun, Litao
Abstract : A facile strategy is introduced to realize the transition of nanoparticle decorated graphene films from water-adhesion surface to water-repellent surface. Abstract : Herein, a facile strategy is introduced to realize the transition of graphene films from a water-adhesion surface (adhesive pressure of 541.5 Pa) to a water-repellent surface (adhesive pressure of ∼0 Pa) via decoration of carbon nanoparticles. Cassie impregnating wetting state and Cassie state are used to explain highly adhesive effect and strong repelling effect, respectively. Droplet impacting experiments demonstrate that the as-prepared graphene films have a stable structure, which is beneficial for their applications.